2005
DOI: 10.3748/wjg.v11.i11.1623
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic changes in the lower esophageal sphincter influencing the result of anti-reflux surgical interventions in chronic gastroesophageal reflux disease

Abstract: AIM:With the availability of a minimally invasive approach, anti-reflux surgery has recently experienced a renaissance as a cost-effective alternative to life-long medical treatment in patients with gastroesophageal reflux disease (GERD). We are not aware of the fact whether reflux episodes causing complaints for a long time i.e., at least for one year are associated with metabolic changes in the lower esophageal sphincter, and if so, whether these may influence functional results achieved after anti-reflux su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…However, the fact that the standard chronological sequence of symptoms described by several authors in that long-lasting reflux is followed by dysphagia (and never vice versa) seems to suggest that achalasia might be a consequence of GERD. This theory is supported by Altorjay et al, 8 who found enteric ganglionitis and smooth muscle hypertrophy in the muscle samples of the LES of reflux patients. These morphological changes, which are characteristic of achalasia, could be interpreted as consequences of long-term reflux episodes.…”
Section: Introductionmentioning
confidence: 57%
See 2 more Smart Citations
“…However, the fact that the standard chronological sequence of symptoms described by several authors in that long-lasting reflux is followed by dysphagia (and never vice versa) seems to suggest that achalasia might be a consequence of GERD. This theory is supported by Altorjay et al, 8 who found enteric ganglionitis and smooth muscle hypertrophy in the muscle samples of the LES of reflux patients. These morphological changes, which are characteristic of achalasia, could be interpreted as consequences of long-term reflux episodes.…”
Section: Introductionmentioning
confidence: 57%
“…Altorjay et al 8 , 15 reported very interesting observations by analyzing LES muscle specimens of reflux patients and comparing them to a control group. They found hypertrophy-like changes or (more specifically) a significant increase in the concentration of structural protein S-100 and myofibrillar protein troponin I in the LES muscle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study showed that antineuronal antibodies of very similar properties were found in the serum of both achalasia and GERD patients, therefore one can assume that the two diseases may not appear independantly of one another, but they may have common autoimmun mechanisms in their pathogenesis [2]. In another study, comparing LES muscle samples of reflux patients with those of a control group, Altorjay et al revealed that reflux patients had enteric ganglionitis and smooth muscle hypertrophy at the gastroesophageal junction, and they suggested that these morphological changes might result in various functional esophageal diseases [3]. The theory that GERD could be an etiologic factor in the development of achalasia was first proposed by Smart et al in 1986, who described 5 patients presenting with reflux, who subsequently developed achalasia over the years [4].…”
Section: Introductionmentioning
confidence: 99%
“…Among our own untreated achalasia cases we also had one patient with concomitant Barrett's esophagus and one with hiatal hernia. Altorjay et al 8,9 reported an interesting observation after comparing muscle samples taken from the lower esophageal sphincter of reflux patients and those of a control group. They found that reflux patients had smooth muscle hypertrophy and enteric ganglionitis at the gastroesophageal junction, and they suggested that these morphological changes might result in various functional esophageal diseases.…”
mentioning
confidence: 99%